2015
DOI: 10.1371/journal.pone.0135525
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Pre- and Postsynaptic Partners of the Cholinergic C-Boutons in Wild-Type and SOD1G93A Lumbar Motoneurons

Abstract: Large cholinergic synaptic terminals known as C-boutons densely innervate the soma and proximal dendrites of motoneurons that are prone to neurodegeneration in amyotrophic lateral sclerosis (ALS). Studies using the Cu/Zn-superoxide dismutase (SOD1) mouse model of ALS have generated conflicting data regarding C-bouton alterations exhibited during ALS pathogenesis. In the present work, a longitudinal study combining immunohistochemistry, biochemical approaches and extra- and intra-cellular electrophysiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 50 publications
5
33
1
Order By: Relevance
“…In sum, our data could not replicate reported differences in the G93A line (Pullen and Athanasiou, 2009; Herron and Miles, 2012; Saxena et al, 2013; Milan et al, 2015) by showing no change in C-bouton size, and also showed a decrease in C-bouton number and density only at end stage.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In sum, our data could not replicate reported differences in the G93A line (Pullen and Athanasiou, 2009; Herron and Miles, 2012; Saxena et al, 2013; Milan et al, 2015) by showing no change in C-bouton size, and also showed a decrease in C-bouton number and density only at end stage.…”
Section: Resultscontrasting
confidence: 99%
“…This was surprising, as bouton enlargement has been reported in the literature (Pullen and Athanasiou, 2009; Herron and Miles, 2012; Saxena et al, 2013; Milan et al, 2015) and has been interpreted as an example of an ALS disease change that influences motoneuron excitability. It is important to mention that our investigation, as opposed to most studies on this topic (Table 1), was based on large samples of WT and G93A motoneurons supported by statistical power analysis and was conducted with blinding to avoid potential bias.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We have also demonstrated that ErbB2 and ErbB4 receptors are present in the presynaptic compartment, suggesting that NRG1 acts as a retrograde signalling molecule in C-type synapses. C-boutons are scarcely investigated structures19, which have been reported to suffer plastic changes in sick MNs after spinal cord injury2021, peripheral nerve lesion22, and amyotrophic lateral sclerosis (ALS)1823242526272829. In addition, mutations in S1R are considered risk factors for familial ALS, and abnormal accumulations of this protein in C-terminals have also been observed in patients with sporadic ALS303132.…”
mentioning
confidence: 99%